UV-C light irradiation effects on two rose cultivars infected with Botrytis cinerea - Eduardo Espejel-Maycotte; Ma de Lourdes Arevalo-Galarza; Jose Alfredo Carrillo-Salazar; José Refugio Lomelí-Flores; Victoria Ayala-Escobar; Luis Francisco Salomé-Abarca (Ornamental Horticulture)
Gray mold (Botrytis cinerea Pers.: Fr) is one of the most important diseases that cause great economic losses in cut roses. Chemical fungicides are widely used for disease management. However, these products have a large accumulation of residues and select strains resistant to pathogens and pesticides. In this context, the irradiation of plants with UV-C light (254 nm) is an effective treatment for the control of several phytopathogens. In this study, the in vitro effect of three doses of UV-C light (1.0, 1.5, and 2.0 kJ m-2) on conidia germination and B. cinerea mycelial growth was evaluated. In addition, in vivo trials were carried out on two white rose cultivars “Polar Star” and “Proud”. For this, the stems of the roses were irradiated with UV-C light before inoculation of B. cinerea or inoculated directly with irradiated conidia. The in vitro experiments showed inhibition of more than 90% of conidia germination and the total inhibition mycelial growth, at any of the doses evaluated. In addition, infection of rosebuds was significantly reduced or avoided when they were inoculated with irradiated conidia. When roses were irradiated with the same doses and inoculated with viable conidia, symptoms appeared more quickly and differences between varieties were more evident. The histological analysis of the rose petals showed that the petals of the roses cv. Proud had thicker abaxial and adaxial epidermis, with numerous elongated cone-shaped papillae, which may confer greater tolerance to Botrytis infections.